2005
DOI: 10.1063/1.1888034
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate of silicon nanowires

Abstract: We have measured the growth rate of silicon nanowires (SiNWs), which were grown at temperatures between 365 and 495 °C via the vapor-liquid-solid (VLS) mechanism. We grew SiNWs using gold as catalysts and monosilane (SiH4) as a vapor phase reactant. Observing SiNWs by means of transmission electron microscopy, we have found that SiNWs with smaller diameters grow slower than those with larger ones, and the critical diameter at which growth stops completely exists. We have estimated the critical diameter of SiNW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
94
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 18 publications
17
94
2
Order By: Relevance
“…The apex angle is determined by the relative rates of radial and axial growth, as illustrated in Figure 3d. The selective influence of catalyst nanoparticle size on axial growth rate as reported for nanowires 10 likely plays a significant role in the controlled variation of apex angles. We hope that this work will generate further interest in and enable more detailed investigations of the shape-and structure-dependent properties of semiconductor nanocones.…”
mentioning
confidence: 83%
“…The apex angle is determined by the relative rates of radial and axial growth, as illustrated in Figure 3d. The selective influence of catalyst nanoparticle size on axial growth rate as reported for nanowires 10 likely plays a significant role in the controlled variation of apex angles. We hope that this work will generate further interest in and enable more detailed investigations of the shape-and structure-dependent properties of semiconductor nanocones.…”
mentioning
confidence: 83%
“…Considering the Gibbs-Thompson common framework for VLS growth, the growth rate becomes diameter (d) dependent, [45][46][47] …”
mentioning
confidence: 99%
“…The improvement in growth could be due to heating of the substrate by a current induced by the repeated striking of the plasma. It has been shown that the growth rate of silicon nanowires improves with increasing temperature [12]. The slight heating of the substrate by a repeatedly induced current would increase the temperature of the centre of the substrate to conditions more favourable to nanowire growth.…”
Section: Discussionmentioning
confidence: 99%